Eklezjalność Ruchu Światło–Życie - Kupny, Józef (Śląskie Studia Historyczno-Teologiczne, 2006)
The level of faith and religious practices in today’s Poland is uniquely stable. Even after 1989, after various political, economic, and social changes have been initiated, the mechanisms of secularization have not really taken root as they have in many Europeans where they made many quit their religious practices. Nevertheless, the symptoms of leaving the path of religion are being observed already among the younger generation living in big cities. What’s clear is that even though the level of religiousness has not changed over the last twenty years, it is more and more clear that the process of un-ecclesiastical attitudes is progressing. Already two-fifths of the entire population of adult Poles emphasizes privacy, selectivity, and independence of their faith. In that light, the existence and subsequent development of Light and Life Movement is a noteworthy phenomenon, as it expresses the opposite trend – namely that of ecclesiastically-oriented religiousness. In the article the author takes an attempt, based on empirical research conducted, to show a condition and level of ecclesiasticism of the members of Light and Life Movement. Ecclesiasticism of the members of Light and Life Movement studied in terms of religious practices, an attachment to a parish, an acceptance of a religious mission of a priest, and an acceptance of a religious doctrine, has appeared as a very vital one. Undoubtedly, the hard work to make members of Light and Life Movement into the faithful ones carried on in small parochial groups and during summer retreats is a very important factor. Studies confirm that ecclesiasticism of members of Light and Life Movement remains firm independently from time and level of initiation.